Respuesta :
Hello,
4x+8y=20
-4x+2y=-30
What you can do here is add both equations together, so that 4x (from the 1st equation) and -4x (from the second equation) cancel out.
After doing that, you get
10y = -10
Therefore, y = -1.
Now, use y = -1 in the original equations.
4x + 8y = 20
4x + 8(-1) = 20
4x-8 = 20
4x = 28
x = 7
You also want to confirm your answers by plugging them in the other equation just to make sure.
-4x + 2y = -30
-4(7) + 2(-1) = -28 - 2 = -30
So, x = 7, and y = -1.
Hope this helped! :)
4x+8y=20
-4x+2y=-30
What you can do here is add both equations together, so that 4x (from the 1st equation) and -4x (from the second equation) cancel out.
After doing that, you get
10y = -10
Therefore, y = -1.
Now, use y = -1 in the original equations.
4x + 8y = 20
4x + 8(-1) = 20
4x-8 = 20
4x = 28
x = 7
You also want to confirm your answers by plugging them in the other equation just to make sure.
-4x + 2y = -30
-4(7) + 2(-1) = -28 - 2 = -30
So, x = 7, and y = -1.
Hope this helped! :)
4x + 8y = 20
-4x + 2y = -30
Adding the equations,
4x + 8y + (-4x + 2y) = 20 + (-30)
4x + 8y - 4x + 2y = 20 - 30
10y = -10
y = [tex] \frac{-10}{10} [/tex]
y = -1
Substituting the value of y in the first equation,
4x + 8y = 20
4x + (8 * -1) = 20
4x - 8 = 20
4x = 20 + 8
4x = 28
x = [tex] \frac{28}{4} [/tex]
x = 7
Hence, x is 7 and y is -1.
-4x + 2y = -30
Adding the equations,
4x + 8y + (-4x + 2y) = 20 + (-30)
4x + 8y - 4x + 2y = 20 - 30
10y = -10
y = [tex] \frac{-10}{10} [/tex]
y = -1
Substituting the value of y in the first equation,
4x + 8y = 20
4x + (8 * -1) = 20
4x - 8 = 20
4x = 20 + 8
4x = 28
x = [tex] \frac{28}{4} [/tex]
x = 7
Hence, x is 7 and y is -1.